Prevalence and Pregnancy Outcome of Gestational Diabetes Mellitus Among Bangladeshi Urban Pregnant Women - Mannan, MA; Rahman, MH; Ara, I; Afroz, H (Journal of Medicine, 2012)
Objective: To assess the prevalence of gestational diabetes mellitus (GDM) among the pregnant women of Dhaka city and to find out the consequences or effects of GDM on pregnancy outcome. Materials and methods: This was a descriptive type of cross sectional study followed by cohort type of study, conducted in different hospitals in Dhaka city. Initially 960 pregnant women of 24th to 28th weeks were selected purposively; plasma glucose was measured at fasting and two hours after taking 75g oral glucose load. Modified method of Carpenter and Coustan criteria was followed to diagnose GDM. For each GDM case diagnosed, one non-GDM pregnant women was taken as control after matching age and parity. Both groups were followed up to 4 wks after delivery to find out maternal and neonatal mortality and morbidities. Results: Out of 960 pregnant women 72 were GDM positive (7.5%).There was no maternal mortality but morbidities like hydramnions (p<0.001)), pre-eclampsia (p<0.001)), urinary tract infection (p<0.05), puerperial sepsis (p<0.05)) and surgical interventions (p<0.001) were more prevalent in GDM compared to non-GDM groups. The prevalence of antipartum haemorrhage, post partum haemorrhage, and eclampsia did not vary between the groups. There was one still birth, one perinatal mortality (due to respiratory distress syndrome) and one congenital anomaly observed in neonates of GDM mothers. More pre-term (p<0.01), post-term (p<0.01), low birth weight (p<0.001) and macrosomic (p<0.001) babies were found among the babies of GDM mothers than non-GDM mothers. More babies also suffered from neonatal jaundice (p<0.05) and respiratory distress syndrome (p<0.05) in GDM groups than non GDM groups. Conclusion: The prevalence of GDM in urban Bangladeshi population is about 7.5%. Maternal morbidities like hydramnios, pre-eclampsia, infections and operative interventions were observed more in GDM mothers. Pre-term, post-term and LBW babies alone with perinatal morbidities like respiratory distress syndrome, macrosomia and neonatal jaundice were more common in babies of GDM mothers. DOI: http://dx.doi.org/10.3329/jom.v13i2.12749 J Medicine 2012; 13 : 147-151